Веб – сайт як метод інформаційної реклами - Уляна, Ярка; Білецька, Наталя (Видавництво Львівської політехніки, 2018)
This article describes the benefits of using a website to effectively promote products and services in the online space. Without this, it is difficult to succeed in a competitive struggle in a market economy. The fact that the institution is represented in the Internet space depends on a significant part of its success
Keywords: Інтернет-реклама; маркетинг; інтернет-простір; інформатизація; комп’ютеризація